UPAYA GURU PPKN DALAM MENINGKATKAN PENGETAHUAN PESERTA DIDIK TENTANG KEBHINEKAAN PADA MATERI BHINEKA TUNGGAL IKA KELAS X DI SMA SWASTA HKBP SIDORAME MEDAN - Christin Hotmauli Br Simbolon; Monalisa Marta Siaahan; Hotmaida Simanjuntak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the efforts of Civic Education (PPKn) teachers in improving students' understanding of diversity in the material of Bhinneka Tunggal Ika in class X at HKBP Sidorame Private Senior High School, Medan. The background of this study is based on the importance of students’ understanding of diversity values as part of character building to create a tolerant, inclusive society that respects differences. This study uses a qualitative approach with a descriptive method. The subjects of this study consist of PPKn teachers and tenth-grade students. Data collection techniques were carried out through observation, interviews, and documentation. The data obtained were then analyzed through the stages of data reduction, data display, and conclusion drawing. The results of the study indicate that the efforts made by PPKn teachers in improving students' understanding of diversity include the use of various teaching methods, such as group discussions, question-and-answer sessions, and providing concrete examples in daily life. In addition, teachers also utilize relevant learning media and instill values of tolerance and mutual respect in the learning process. However, there are several obstacles faced, such as limited instructional time and differences in students’ levels of understanding. Based on the results of the study, it can be concluded that the efforts of PPKn teachers have a significant role in improving students' understanding of diversity. Therefore, innovation and consistency in the learning process are needed so that the objectives of civic education can be achieved optimally.